Understanding the quality of life of family carers of people with dementia: Development of a new conceptual framework. (25th September 2018) - Daley, Stephanie; Murray, Joanna; Farina, Nicolas; Page, Thomas E.; Brown, Anna; Basset, Thurstine; Livingston, Gill; Bowling, Ann; Knapp, Martin; Banerjee, Sube
Abstract : Background: Dementia is a major global health and social care challenge, and family carers are a vital determinant of positive outcomes for people with dementia. This study's aim was to develop a conceptual framework for the Quality of Life (QOL) of family carers of people with dementia. Methods: We studied family carers of people with dementia and staff working in dementia services iteratively using in‐depth individual qualitative interviews and focus groups discussions. Analysis used constant comparison techniques underpinned by a collaborative approach with a study‐specific advisory group of family carers. Results: We completed 41 individual interviews with 32 family carers and nine staff and two focus groups with six family carers and five staff. From the analysis, we identified 12 themes that influenced carer QOL. These were organised into three categories focussing on person with dementia, carer, and external environment. Conclusions: For carers of people with dementia, the QOL construct was found to include condition‐specific domains which are not routinely considered in generic assessment of QOL. This has implications for researchers, policy makers, and service providers in addressing and measuring QOL in family carers of people with dementia.